2022
DOI: 10.3390/rs14246273
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Use/Land Cover Change on Ecological Quality during Urbanization in the Lower Yellow River Basin: A Case Study of Jinan City

Abstract: Rapid urbanization in the lower Yellow River basin has greatly contributed to the socio-economic development of Northern China, but it has also exacerbated land use/land cover change, with significant impacts on ecology. Ecological quality is a comprehensive spatial and temporal measure of an ecosystem’s elements, structure and function, reflecting the ecological state under external pressures. However, how land use/land cover change affects the ecological quality during urbanization has rarely been explored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…Landuse dynamics refers to the extent of dynamic changes occurring among various landuse types and finds widespread application in land monitoring and management [3]. Due to the impact of human activities, landuse types are subject to significant transformations across various regions and periods.…”
Section: Landuse Dynamic Degreementioning
confidence: 99%
See 2 more Smart Citations
“…Landuse dynamics refers to the extent of dynamic changes occurring among various landuse types and finds widespread application in land monitoring and management [3]. Due to the impact of human activities, landuse types are subject to significant transformations across various regions and periods.…”
Section: Landuse Dynamic Degreementioning
confidence: 99%
“…In addition, it is essential to strengthen field testing and refine the evaluation model accordingly. (3) This study primarily focused on constructing an ESP within the study area. Future work would adopt a more comprehensive approach, considering ecological security from local and cross-regional perspectives.…”
Section: Limitations and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen [11] and Gao [12] pinpoint urban expansion and land transfer as key influencers. Yu et al found that urban expansion, along with farmland protection policies, can harm ecological quality [13], while Chen et al identified the critical role of forests and hydrological systems in ecosystem services [14]. Different urban agglomerations exhibit varying impacts.…”
Section: Introductionmentioning
confidence: 99%
“…As the social economy, urbanization, and industrialization rapidly progress, human land use practices are undergoing consequential evolution [5,6]. However, the overexploitation and wastage of land resources are prevalent in today's world, exacerbating conflicts between humans and land and giving rise to severe ecological and environmental issues, such as vegetation destruction [5], soil erosion [7], land desertification, and soil pollution [8]. Numerous studies have demonstrated that land use and cover change play a crucial role in influencing ecological and environmental transformations [9][10][11].…”
Section: Introductionmentioning
confidence: 99%